TINJAUAN GEOTEKNIK KEAMANAN REMBESAN DAN PEMBEBANAN GEMPA PADA STABILITAS LERENG (Studi: Bendungan Way Sekampung) - R. Abadirulian Ervantara; Ahmad Rifa'i; Iman Satyarno (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2022)
Abstract : Way Sekampung Dam is built to optimize the utilization of the Way Sekampung watershed. It is classified as an embankment dam with upright core which is following with a high risk of failure. The research of dam slope stability become an effort to fulfill dam safety. This study is based on the effects of seepage and seismicity. The seepage review is focused on what is the safety of the dam against potential piping, while for seismicity it is carried out under earthquake loading which using a modified earthquake coefficient approach. Based on the calculation of the seepage modeling using SEEP/W at the flood water level (FWL) and normal water level (NWL) obtained a value of the calculated safety factor (SFcal) of ≥ SFmin = 4 and, it can be said to be safe against piping. Slope stability modeling with SLOPE/W at post construction, flood water level (FWL),normal water level (NWL), and low water level (LWL), under earthquake loading conditions, it is found that the calculated safety factor (SFcal) varies in each loading condition. In the OBE loading conditions; the calculated safety factor value (SFcal) is greater than SFmin, indicating that the slope stability at the Way Sekampung Dam is safe. The simulation with MDE loading conditions, show results of the dam slope stability modeling in several variation resulted in SFcal < SFmin. This shows that the slope stability at the Way Sekampung Dam is not safe, have the potential to experience damage and collapse. Keywords: embankment dam, slope stability, seepage, earthquake, SEEP/W and SLOPE/W